AICCRA-Kenya university partners modeling training: Capacity strengthening for university PIs - Nderi, Alex Nduah; Nzuki, Esther Ndumi (2025)
In alignment with AICCRA’s country-level scaling and capacity-strengthening goals in Kenya, a two-day hands-on modeling training was conducted for Principal Investigators (PIs) from Chuka University, Murang’a University of Technology, and Taita Taveta University. Delivered by experts from KALRO and the Alliance of Bioversity International & CIAT, the training introduced climate, soil, pest, and crop-climate modeling tools and workflows. The objective was to enhance university-led research, teaching, and outreach in climate-smart agriculture (CSA). The training fostered collaboration among institutions and supported AICCRA Kenya’s broader agenda of improving climate information services and scaling CSA innovations through national partnerships.